Analysis of Desorption Characteristics of Silica Gel-Water Pair In Solar Collector of A Solar Adsorption Refrigeration System - Karthick S, Shrivathsan C S, DadiYugesh Naidu, S Sreyas, C E TharunNatrajan (International Journal of Advanced Science and Technology, 2020)
This investigation involves analyzing the desorption characteristics of silica gel-water pair in the solar collector of a Solar Adsorption Refrigeration System. The conditions for silica gel to act as an adsorbent have been identified experimentally by observing the transient behavior of the system. Results indicate an exponential variation of the desorption kinetics. In this study, reaction kinetics have been studied for three different heat fluxes to understand the variation of a parameter namely,the percentage of water present per unit mass of silica gel with heat flux. The results based on the plots of desorption reveal similar trends for the values of heat flux tested. Utilizing curve fitting technique, an expression describing the reaction and the rate constant of the reaction has been presented.